Tree genetic resources at risk in South America: A spatial threat assessment to prioritize populations for conservation - Zonneveld, M.J. van; Thomas, E.; Castañeda Álvarez, Nora P.; Damme, V. van; Alcázar, C.; Loo, J.; Scheldeman, Xavier (Wiley, 2018)
Background Humans threat the populations of tree species by overexploitation, deforestation, land use change, and climate change. We present a novel threat assessment at intraspecific level to support the conservation of genetic resources of 80 socioeconomically viable tree species in South America. In this assessment, we evaluate the threat status of Ecogeographic Range Segments (ERSs). ERSs are groups of populations of a specific species in a certain ecological zone of a particular grid cell of a species’ geographic occupancy. Methods We used species location records to determine the species distributions and species‐specific ERSs. We distinguished eight threat situations to assess the risk of extirpation of the ERSs of all 80 species. These threat situations were determined by large or little tree cover, low or high human pressure, and low or high climate change impact. Available layers of tree cover and threats were used to determine the levels of fragmentation and direct human pressure. Maxent niche modelling with two Global Circulation Models helped determining climate change impact by the 2050s. Results When all 80 species are considered, in total, 59% of the ERSs are threatened by little tree cover or high human pressure. When climate change is also considered, then 71‐73% of the ERSs are threatened. When an increased risk of extirpation of populations outside protected areas is considered, then 84–86% of the ERSs are threatened. Seven species warrant special attention because all their ERSs are threatened across their whole distribution in South America: Balfourondendron riedelianum, Cariniana legalis, Dalbergia nigra, Handroanthus pulcherrimus, Pachira quintana, Prosopis flexuosa, and Prosopis pallida. Conclusions Our results confirm the urgency to set up a regional action plan for the conservation of tree genetic resources in South America. With this threat assessment, we aim to support governments and organizations who are taking up this task.